Potential for host-symbiont communication via neurotransmitters and neuromodulators in an aneural animal, the marine sponge Amphimedon queenslandica - Xiang, Xueyan; Vilar Gomez, Arturo A.; Blomberg, Simone P.; Yuan, Huifang; Degnan, Bernard M.; Degnan, Sandie M. (Frontiers in Neural Circuits, 2023)
Interkingdom signalling within a holobiont allows host and symbionts to communicate and to regulate each other's physiological and developmental states. Here we show that a suite of signalling molecules that function as neurotransmitters and neuromodulators in most animals with nervous systems, specifically dopamine and trace amines, are produced exclusively by the bacterial symbionts of the demosponge Amphimedon queenslandica. Although sponges do not possess a nervous system, A. queenslandica expresses rhodopsin class G-protein-coupled receptors that are structurally similar to dopamine and trace amine receptors. When sponge larvae, which express these receptors, are exposed to agonists and antagonists of bilaterian dopamine and trace amine receptors, we observe marked changes in larval phototactic swimming behaviour, consistent with the sponge being competent to recognise and respond to symbiont-derived trace amine signals. These results indicate that monoamines synthesized by bacterial symbionts may be able to influence the physiology of the host sponge.